Identification of Differentially Expressed Genes Using cDNA-AFLP During Six Days In Vitro Tuberization of Potato - Nono Carsono; Christian Bachem (Zuriat, 2003)
Tuberization in potato is a complex developmental process resulting in the differentiation of stolon into the storage organ, tuber. During tuberization, change in gene expression has been known to occur. To study gene expression during tuberization over the time, in vitro tuberization system provides a suitable tool, due to its synchronous in tuber formation. An early six days axillary bud growing on tuber induction medium is a crucial development since a large number of genes change in their expression patterns during this period. In order to identify, isolate and sequencing the genes which displaying differential pattern between tuberizing and non-tuberizing potato explants during six days in vitro tuberization, cDNA-AFLP fingerprint, method for the visualization of gene expression using cDNA as template which is amplified to generate an RNA-fingerprinting, was used in this experiment. Seventeen primer combinations were chosen based on their expression profile from cDNA-AFLP fingerprint. Forty five TDFs (transcript derived fragment), which displayed differential expressions, were obtained. Tuberizing explants had much more TDFs, which developmentally regulated, than those from non tuberizing explants. Seven TDFs were isolated, cloned and then sequenced. One TDF did not find similarity in the current databases. The nucleotide sequence of TDF F showed best similarity to invertase ezymes from the databases. The homology of six TDFs with known sequences is discussed in this paper.